GE_GERICHTE C/30726/2010 vom 18. Oktober 2013 - GE Cour de justice (2013)
ACTION EN PAIEMENT; NATURE JURIDIQUE; DOMMAGES-INTÉRÊTS; EXÉCUTION DE L'OBLIGATION | CPC.221.1.A; CO.394; CO.398.2; CO.412; CO.184; CO.201.1; CO.197; CC.924.2